Task-space coordinated tracking of multiple heterogeneous manipulators via controller-estimator approaches. Issue 15 (October 2016) - Ge, Ming-Feng; Guan, Zhi-Hong; Yang, Chao; Chen, Chao-Yang; Zheng, Ding-Fu; Chi, Ming
Abstract: This paper studies the task-space coordinated tracking of a time-varying leader for multiple heterogeneous manipulators (MHMs), containing redundant manipulators and nonredundant ones. Different from the traditional coordinated control, distributed controller-estimator algorithms (DCEA), which consist of local algorithms and networked algorithms, are developed for MHMs with parametric uncertainties and input disturbances. By invoking differential inclusions, nonsmooth analysis, and input-to-state stability, some conditions (including sufficient conditions, necessary and sufficient conditions) on the asymptotic stability of the task-space tracking errors and the subtask errors are developed. Simulation results are given to show the effectiveness of the presented DCEA.